Maternal Intensive Care Unit Admission as an Indicator of Severe Acute Maternal Morbidity: A Population-Based Study. (14th May 2021) - Godeberge, Charlotte; Deneux-Tharaux, Catherine; Seco, Aurélien; Rossignol, Mathias; Chantry, Anne Alice; Bonnet, Marie-Pierre; ,
Abstract : BACKGROUND: Severe acute maternal morbidity (SAMM) accounts for any life-threatening complication during pregnancy or after delivery. Measuring and monitoring SAMM seem critical to assessing the quality of maternal health care. The objectives were to explore the validity of intensive care unit (ICU) admission as an indicator of SAMM by characterizing the profile of women admitted to an ICU and of their ICU stay, according to the association with other SAMM criterion. METHODS: We performed a secondary analysis of the 2540 women with SAMM included in the epidemiology of severe acute maternal morbidity (EPIMOMS) multiregional prospective population-based study (2012–2013, n = 182, 309 deliveries). The EPIMOMS definition of SAMM, based on national experts' consensus, is a combination of diagnosis, organ dysfunctions, and intervention criteria, including ICU admission. Among women with SAMM, we identified characteristics associated with maternal ICU admission with or with no other SAMM criterion compared with ICU admission, by using multivariable multinomial logistic regression models. RESULTS: Overall, 511 women were admitted to an ICU during or up to 42 days after pregnancy, for a population-based rate of 2.8 of 1000 deliveries (511/182, 309; 95% confidence interval [CI], 2.6-3.1); 15.5% of them (79/511; 95% CI, 12.4-18.9) had no other SAMM criterion compared with ICU admission. Among women with SAMM, the odds of ICU admission with no other morbidity criterion were increased in women with preexisting medical conditions (adjusted odds ratio (aOR), 2.13; 95% CI, 1.17-3.86) and cesarean before labor (aOR, 3.12; 95% CI, 1.47-6.64). Women admitted to ICU with no other SAMM criterion had more often decompensation of a preexisting condition, no interventions for organ support, and a shorter length of stay than women admitted with other SAMM criteria. CONCLUSIONS: Among women with SAMM, 1 in 5 is admitted to an ICU; 15.5% of those admitted in ICU have no other SAMM criterion and a less acute condition. These results challenge the use of ICU admission as a criterion of SAMM.